Plasma omega-3 PUFA and white matter mediated executive decline in older adults - Bowman, Gene L.; Dodge, Hiroko; Mattek, Nora; Barbey, Aron K.; Silbert, Lisa C.; Shinto, Lynne; Howieson, Diane; Kaye, Jeffrey; Quinn, Joseph (Frontiers in Aging Neuroscience, 2013)
Introduction: Cross-sectional studies have identified long chain omega-3 polyunsaturated fatty acids (eicosapentaenoic acid 20:5n-3 and docosahexaenoic acid 22:6n-3 (O3PUFA) in association with fewer white matter lesions and better executive function in older adults. We hypothesized that O3PUFA are associated with less executive decline over time and that total white matter hyperintensity volume (WMH) mediates the putative association. Methods: Eighty-six non-demented older adults were followed over 4 years after measurement of plasma O3PUFA with annual evaluations of cognitive function. A subset of these participants also had brain MRI of total WMH available to conduct a formal mediation analysis of a putative relationship between O3PUFA and cognitive function. Results: Mean age at baseline was 86, 62% were female and 11% carried the APOE4 allele. Each 100 μg/ml increase in plasma O3PUFA associated with 4 seconds less change in executive decline per year of aging (p = 0.02, fully adjusted model). O3PUFA was not associated with verbal memory or global cognitive changes. The significance of the association between O3PUFA and better executive function was lost once WMH was added to the regression model. Conclusion: Executive decline with age appears to be a cognitive domain particularly sensitive to plasma O3PUFA in longitudinal examination. O3PUFA may modulate executive functioning by mechanisms underlying the development of WMH, a biologically plausible hypothesis that warrants further investigation.